MODERN TECHNOLOGIES IN PHYSICAL EDUCATION - Irmatov, Fozil Muminovich (Educational Research in Universal Sciences, 2023)
Accelerated development of science and production, along with the economic upheaval of the society, provides a fundamental change in the content of social relations. In addition, a great deal of attention is paid to the introduction of a technological approach to social issues, including in the economic field.